A multicenter randomized comparison between intravenous and perineural dexamethasone for ultrasound-guided infraclavicular block - Prangmalee Leurcharusmee (2018)
© 2016 American Society of Regional Anesthesia and Pain Medicine. Background and Objectives This multicenter, randomized trial compared intravenous (IV) and perineural (PN) dexamethasone for ultrasound (US)-guided infraclavicular brachial plexus block. Our research hypothesis was both modalities would result in similar durations of motor block. Methods One hundred fifty patients undergoing upper limb surgery with US-guided infraclavicular block were randomly allocated to receive IV or PN dexamethasone (5 mg). The local anesthetic agent (35 mL of lidocaine 1%-bupivacaine 0.25% with epinephrine 5 μg/mL) was identical in all subjects. Patients and operators were blinded to the nature of IV and PN injectates. During the performance of the block, the performance time, number of needle passes, procedural pain, and complications (vascular puncture, paresthesia) were recorded. Subsequently, a blinded observer assessed the success rate (defined as a minimal sensorimotor composite score of 14 of 16 points at 30 minutes), onset time as well as the incidence of surgical anesthesia (defined as the ability to complete surgery without local infiltration, supplemental blocks, IV opioids, or general anesthesia). Postoperatively (at 24 hours), the blinded observer contacted patients with successful blocks to enquire about the duration of motor block, sensory block, and postoperative analgesia. The main outcome variable was the duration of motor block. Results No intergroup differences were observed in terms of technical execution (performance time/number of needle passes/procedural pain/complications), onset time, success rate, and surgical anesthesia. However, compared to its IV counterpart, PN dexamethasone provided 19% to 22% longer durations for motor block (15.7 ± 6.2 vs 12.9 ± 5.5 hours; P = 0.009), sensory block (16.8 ± 4.4 vs 13.9 ± 5.4 hours; P = 0.002), and postoperative analgesia (22.1 ± 8.5 vs 18.6 ± 6.7 hours; P = 0.014). Conclusions Compared with its IV counterpart, PN dexamethasone (5 mg) provides a longer duration of motor block, sensory block, and postoperative analgesia for US-guided infraclavicular block. Future dose-finding studies are required to elucidate the optimal dose of dexamethasone.